Unraveling communication effects on small-scale vendors’ businesses in Kigali’s Ejoheza Modern Market - Jean Baptiste Manirakiza; David Majariwa; Johnson Ocan (Annals of Management and Organization Research, 2025)
Purpose: The research aimed to understand how small-scale vendors exchange with their customers from various linguistic backgrounds. It particularly sought to explore how language proficiency influences business interactions and customer satisfaction in the Ejoheza Modern Market, Kigali. Methods: Using a qualitative approach, the study investigated the language preferences and communication practices of small-scale vendors. Data were collected through direct observation and interviews with selected vendors to identify the main languages used in daily transactions and coping mechanisms adopted when facing language barriers. Results: The findings revealed that all vendors can easily speak Kinyarwanda, but only a few of them can communicate in English and French. This limitation affects their interaction with non-Kinyarwanda-speaking customers, often leading to communication breakdowns. To address this challenge, vendors rely on translation applications on their phones or seek assistance from interpreters to facilitate exchanges. Conclusion: The study concludes that language proficiency significantly influences vendors’ ability to attract and serve diverse customers, which in turn affects sales and market inclusivity. Limitations: The study was limited to Ejoheza Modern Market and did not include other markets in Kigali, which restricts the generalization of the findings. Contribution: This study highlights the critical role of language skills in enhancing small-scale vendors’ business success. It recommends establishing affordable language training programs to empower vendors, improve customer relations, and promote inclusive economic growth in Rwanda’s urban markets.